Identification of Hazardous Glacial Lakes in the Yarlung Zangbo River Basin Based on Lakes Changes Determined Using Google Earth Engine - Sun, Xiaodong; Cao, Bo; Pan, Baotian; Li, Kaiji; Zhao, Xuanru; Guan, Weijin (Frontiers in Earth Science, 2022)
Glaciers have melted rapidly in the Yarlung Zangbo River Basin due to recent climate change, which has accelerated the expansion of glacial lakes. We performed a systematic survey of glacial lakes in the Yarlung Zangbo River Basin using the Google Earth Engine platform. This allowed us to map the distribution and monitor the evolution of glacial lakes over seven time periods from 1990 to 2020, using more than 140 Landsat Thematic Mapper and Operational Land Imager images at a 30-m resolution. The results show that there were 2088 glacial lakes in 2020, with a total area of 245.87 km2, mainly distributed at elevations of 3800 to 5800 m above sea level. From 1990 to 2020, the Yarlung Zangbo River Basin glacial lakes expanded by approximately 1.81 km2·a-1. A total of 153 glacial lakes in the Yarlung Zangbo River Basin were assessed. The assessment shows that 153 glacial lakes were divided into very high, high, medium, low and very low level. The number of glacial lakes in each level is 23, 22, 32, 32 and 44 respectively. The very high and high level glacial lakes were mainly found in the Yi’ong Zangbo River Basin, Parlung Zangbo River Basin, the western of the YZRB and Nianchu River Basin. These glacial lakes deserve further attention and monitoring.